(untitled) (Damascus University Journal for engineering sciences, 2026)
The research deals with the roots of myths and their components in modern Arab sculpture, and monitors their impact on the structure of these works, in terms of content, artistic construction, imagination, and aesthetic value, in addition to the main goal of their employment, which reveals either aesthetic and artistic values, or reasons related to understanding The self, the world, and existence, or this employment comes to preserve the values found in the myth, that is, as documentation. This research attempts to reveal the technical and semantic aspects of modern Arab sculpture, especially with regard to the phenomenon of employing myth (in its form and content), then understanding the relationship between myth and art, especially the art of modern Arab sculpture, in addition to knowing the reasons for the interest of the modern Arab sculptor in myth and the methods of employing it. Accordingly, the research was based on several topics, dealing with the myth within the limits of its linguistic and idiomatic definitions, its function and aesthetic dimension, and a reading of models of modern Arab sculpture, those whose positions were inspired by the myth.